Value added products from under-utilised livestock dairy farm resources (wastes): The possibilities and prospects (Indian Journal of Animal Production and Management, 2024)
The major under-utilized resources on livestock farms are the wastes generated as animal dung, urine and  unused or trodden feed and litter wastes like straws. Urine and spent water from washing in milking parlours  constitute the liquid wastes, besides wash water from milk handling yards. Disposal of excreta and other  wastes from animal houses is a bothersome yet crucial activity. Such waste material has a good value  as manure if properly handled. Or, if left not cleared, they can also provide an ideal breeding place for  pathogens and disease carrying insects. The best way is to handle livestock wastes systematically  and produce Value Added Products (VAP) from them in an environment-friendly manner. This is  a big industry already. From the traditional manure, to the cosmetics and medicines, a variety of  such VAPs can be made to enhance the income of the livestock farmers in a sustainable manner;  for such products were recognized by US FDA. These aspects are discussed in this article, which  may be considered as a motivation article, rather than a review.
Keywords: Livestock wastes; climate friendly disposal of wastes; Value Added Products or VAPs; Compost; Biogas; economy of farm wastes